PROFIL WANITA BERCADAR ( Studi Kasus Wanita Salafi di Kelurahan Tangkerang Timur Kecamatan Tenayan Raya Kota Pekanbaru) - Rahayu, Wiga; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study was motivated by the rapid growth of religious groups in Indonesia. One is a group that has a unique salafi movement in clothes. Salafi women predominantly use the robe, robes and veils. Veil has not been fully accepted by society. The aim of this study aims to see the profile of veiled women, the factors that influence women to wear the veil as well as public perception of the veiled women. research sites in the village east tangkerang Pekanbaru city highway Tenayan districts that serve the research subjects were women veiled in the village east Tangkerang many as 6 people. This study is also equipped with key informants that as many as 12 people . collection by interview and observation and then the data were analyzed using descriptive qualitative method. Based on the results of the research will be explained profile veiled woman's life, factors that encourage women to wear a veil which consists of internal factors: the religious orders, of their own accord, knowledge. External factors: family, peers. While the public perception of the veiled women consists of a positive perception: veiled women undergo religious instruction, veil as evidence religius. Negative perceptions: being closed, and a group of hard flow.Keywords: Women, veil, Group, Religion